Glatiramer acetate reverts stress-induced alterations on adult neurogenesis and behavior. Involvement of Th1/Th2 balance - Palumbo, María Laura (2012)
Long-term exposure to stressful situations has deleterious effects on adult neurogenesis, behavior, and the immune system. We have previously shown that stressed BALB/c mice show poor learning performance, which correlates with an increase in the T helper 1/T helper 2 (Th1/Th2) cytokine balance. Glatiramer acetate (GA) can stimulate autoreactive T cells. In this work we investigated the effects of GA treatment on BALB/c mice exposed to chronic mild stress (CMS). Stressed mice exhibited a significant decline in their performance in the open field and Y-maze tasks, which was accompanied by a reduction in dentate gyrus neurogenesis and an altered Th1/Th2 balance. Interestingly, after 6 weeks of CMS exposure administration of GA reestablished normal levels of adult neurogenesis, restored the Th1/Th2 balance, and improved learning performance. These results demonstrate that GA treatment can reverse the learning impairment induced by stress through a mechanism that likely involves the regulation of the cytokine balance and adult neurogenesis.